Kajian stilistika teks bahasa Pedalangan Wayang Purwa gaya Surakarta - Subroto, D. Edi (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2013)
The purpose of this study is to identify and describe the linguistic elements used by writers to obtain specific effects (expressive function) in their creative process. The study applied a descriptive qualitative research model. The results of the study show that in the use of comprehensive and significant linguistic elements, janturan (pathet 6, pathet 9, pathet manyura) appears, especially janturan pathet 6. It is considered comprehensive because all linguistic elements are used together and support the expressive function. In the use of janturan pathet 6, writers illustrate kebinatharaan (the honor of the god Bathara) and the glory of a king, as well as the prosperity and conquest of a kingdom.